Blood glucose to predict symptomatic intracranial hemorrhage after endovascular treatment of acute ischemic stroke with large infarct core: a prospective observational study - Yang, Yujie; Yang, Lihui; Shi, Xiaolei; Ni, Xuan; Fan, Shitao; Xu, Xu; Ma, Jinfu; Yang, Shihai; Wang, Zhixi; Zi, Wenjie; Yang, Dahong; Hao, Yonggang (Frontiers in Neurology, 2024)
Introduction: Symptomatic intracranial hemorrhage (sICH) is a serious complication of acute ischemic stroke (AIS) after endovascular treatment (EVT). Limited data exist regarding predictors and clinical implications of sICH after EVT, underscoring the significance of identifying risk factors to enhance prevention strategies. Therefore, the main objective of this study was to evaluate the incidence of sICH and identify its predictors after EVT in patients with large infarct core-AIS in the pre-circulation stage. Methods: Using data from the EVT for Pre-circulation Large Infarct Core-AIS Study, we enrolled patients who were treated with EVT from the Prospective Multicenter Cohort Study of Early Treatment in Acute Stroke (MAGIC) registry. Baseline demographics, medical history, vascular risk factors, blood pressure, stroke severity, radiographic features, and EVT details were collected. The patients were classified into three groups: without intracranial hemorrhage (ICH), with asymptomatic intracranial hemorrhage (aICH), and sICH, based upon the occurrence of symptomatic intracranial hemorrhage (sICH). The main outcomes were occurrence of sICH according to the Heidelberg Bleeding Classification and functional condition at 90 days. Multivariate logistic regression analysis and receiver operating characteristic (ROC) curves were used to identify independent predictors of sICH after EVT. Results: Patients with sICH had less favorable outcomes than those without intracranial hemorrhage (ICH) and those with aICH (13.8% vs. 43.5% vs. 32.2%, respectively; P < 0.001). Univariate analysis revealed significant differences among the three groups in terms of blood glucose levels at admission, probability of favorable outcomes, incidence of brain herniation, and 90-day mortality.Multifactorial logistic regression analysis revealed that the blood glucose level at admission (odds ratio (OR) 1.169, P < 0.001, confidence interval (CI) 1.076-1.269) was an independent predictor of sICH. A blood glucose level of 6.95 mmol/L at admission was the best predictor of sICH, with an AUC of 0.685 (95% CI: 0.616-0.754). Discussion: Higher blood glucose levels at admission were associated with sICH after EVT in patients with pre-circulation large infarct core AIS. Early Treatment in Acute Stroke (MAGIC) study, the present study aimed to analyze potential predictors of sICH after EVT in patients with pre-circulation large infarct-core AIS.